Мемлекеттік сатып алулар саласындағы құқықтық реттеу ерекшеліктері: пәні және әдістері (Journal of actual problems of jurisprudence, 2018)
The article studies the problems of determining the legal nature of public procurement, namely, from the point of defining the concept of public procurement, the subject and methods of regulation of legal relations arising in the sphere of public procurement. The relevance of the research topic is determined by several factors, based on the need to study the issues of scientific- theoretical, legislative character. Every year in the Republic of Kazakhstan, huge financial resources are allocated for public procurement, which are used by the state for its needs, spreading them through public procurement between potential suppliers. So, at present the public procurement plan is about 2.7 trillion tenge, or 10 billion US dollars. Since public procurement occupies a significant place in the cost of the budget not only in Kazakhstan, but also in most foreign countries, it is an effective tool for managing the economy and developing market relations. Through public procurement, many states fulfill their socio-economic functions, as well as ensure the conduct of scientific research, the creation and implementation of new technologies and developments. The organization of optimal and effective spending of money used for public procurement requires special control, mechanisms and instruments from government agencies. In this regard, the country has general regulatory legal acts such as the Civil Code of the RK, the Budget Code of the RK, the Code of the RK on Administrative Offenses and other special legal acts – the Law of the Republic of Kazakhstan «On Public Procurement» and the Rules for Public Procurement. In this connection, among theorists and practicing specialists there is a dispute about the legal nature of public procurement, which leads to a misconception regarding the legal status of public procurement in a certain sphere of law. The importance of this study is growing due to the fact that in domestic science there is no comprehensive theoretical study of this topic from a legal point of view. This work aims to define the concept, subject and methods for regulating legal relations in the field of public procurement. General scientific, historical and methods of comparative analysis have been used for research purposes. The legal analysis carried out by the authors made it possible to provide recommendations to improve the legal process of dealing with these problems on the national levels. Key words: state, public purchases, equality of parties, disposability.